Study of Compress Strength and Time Setting of Concrete by Additives of Silica Fume and Nano Silica - Ali Hosseini, Afshar; Hossein Hosseini, Seyyed; Reza Abbas Zadeh, Ali (Asian Journal of Chemistry, 2011)
In the present study effects of the silica fume and nano-SiO2 on cement mortars is investigated. Silica fume size is in range of 0.1-0.5 micron and nano-silica is in particle form with 98.31 % of SiO2 in nano scale. The properties of cement mortar are studied at three water/cement ratios of 0.30, 0.35 and 0.50 and three contents of silica fume particles per cement of 5, 10 and 15 %. For evaluation of nano-silica effects on the cement mortar four water/cement ratios of 0.25, 0.30, 0.35 and 0.50 and four contents of nano-SiO2 particles per cement of 5, 10 and 15 % are used. The experimental results show that the compressive strengths of mortars with nano-SiO2 particles are higher than the corresponding mortars containing silica fume for two times of 7 and 28 days. The setting time of mortars with nano-SiO2 particles are less than the corresponding mortars containing ordinary portland cement and micro silica.